A ‘DEADLY’ BENIGN TUMOR: RAPIDLY FATAL RECURRENCE OF ATYPICAL MENINGIOMA - Tasya Lianda Sari; Cindy Yusliani; Riza Pratama Putra; Arindi Maretzka (Magna Neurologica, 2026)
Background: Meningioma is the most common primary CNS tumor. While most are benign (WHO grade I), approximately 15–20% are grade II (atypical) and 1-2% are grade III (anaplastic), carrying a higher recurrence risk. Rapidly fatal recurrence of grade II meningioma remains infrequently reported, particularly in resource-limited settings such as Indonesia. Case Report: A 65-year-old woman with a history of atypical meningioma (WHO grade II) resection eight months earlier presented with decreased consciousness, severe headache, projectile vomiting, and left-sided hemiparesis. Due to the unavailability of the operative report and postoperative imaging from the initial procedure, the Simpson grade and extent of resection could not be determined. Non-contrast head CT revealed a recurrent extra-axial mass in the right temporal region with edema and a midline shift of ±15 mm, suggestive of malignant progression. The patient received supportive therapy without reoperation or adjuvant radiotherapy. Despite a transient improvement, the clinical course deteriorated progressively and led to death on day 19. Discussion: Rapid decompensation is explained by the Monro-Kellie doctrine, whereby the expanding recurrent mass exhausted intracranial compensatory reserve, culminating in fatal herniation. The absence of documented Simpson grade, serial postoperative MRI, adjuvant radiotherapy, and molecular profiling contributed to delayed detection and fatal outcome. Geographic inaccessibility, financial constraints, and low health literacy further impeded surveillance. Conclusion: Grade II meningioma should not be regarded as benign. A structured surveillance protocol; MRI within 48 hours postoperatively, at 4 months, and annually thereafter, combined with Simpson grade documentation and consideration of adjuvant radiotherapy, is essential to prevent fatal recurrence.